please answer this question
Attachments:
![](https://hi-static.z-dn.net/files/d95/8bf95c0fe6320585a480a43bcb5956bd.jpg)
Answers
Answered by
1
Given: 6(4^x+9^x)=13×6^x 6.4^x + 6.9^x = 13×6^x
now divide both sides by 6.6^x we get
6.4^x/6.6^x + 6.9^x/6.6^x = 13×6^x /6.6^x
=> (4/6)^x +(9/6)^x = 13/6=> (2/3)^x +(3/2)^x = 13/6
Substitute diffrent integers and test (using trail and error method)
we will get the answer= 1 and -1
now divide both sides by 6.6^x we get
6.4^x/6.6^x + 6.9^x/6.6^x = 13×6^x /6.6^x
=> (4/6)^x +(9/6)^x = 13/6=> (2/3)^x +(3/2)^x = 13/6
Substitute diffrent integers and test (using trail and error method)
we will get the answer= 1 and -1
Similar questions